Research on the temporal and spatial characteristics, spatial clustering and governance strategies of carbon emissions in cities of Shandong - Yang, Ahui; Zhang, Long; Zhang, ShanZhong; Zhan, Zhe; Shi, Jie (Frontiers in Environmental Science, 2022)
In the face of increasingly severe climate and environmental issues and the context of the "emission peak and carbon neutrality", there is an urgent need for Chinese provinces and cities to accelerate the development of a low carbon transition. However, the level and process of development vary greatly among cities, so practical and feasible city carbon emission characteristics clustering analysis can provide scientific guidance for low carbon emission reduction development. In this paper, 16 cities in Shandong province are selected as the research objects, and the spatial and temporal distribution characteristics of carbon emissions and carbon intensity of each city are firstly analyzed using ArcGIS; then the systematic clustering method is applied to cluster the characteristics of 16 cities in Shandong province, and these cities are classified into four types according to the selected static and dynamic index characteristics: "low economic high carbon", "high economic high carbon", "high economic low carbon" and "low-carbon demonstration". The results show that the classified cities are not fully contiguous geographically, and uniform or zoned low-carbon policies cannot achieve significant results. Finally, after a detailed analysis of the carbon emission characteristics of each of the four categories of cities, targeted policy recommendations to promote low-carbon development are proposed.